2016
DOI: 10.1186/s12917-016-0656-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Mycobacterium bovis in cattle herds of the state of Pernambuco, Brazil

Abstract: BackgroundThe present study aimed to direct detect Mycobacterium bovis in milk (n = 401) and blood (n = 401) samples collected from 401 dairy cows of 20 properties located in the state of Pernambuco, Brazil, by real-time quantitative PCR (qPCR) targeting the region of difference 4 (RD4). Risk factors possibly associated with bovine tuberculosis (BTB) were also evaluated.ResultsOf the 802 samples analyzed, one milk (0.25 %) and eight blood (2 %) samples were positive for M. bovis in the qPCR and their identitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…32 A variable incidence of bTB may effect through several modes like the geographical position features; Agroecological system; public health condition for humans and animals; herd size, farm management and grazing practice; age, breed, gender and body condition score of animals; compelled organizing schemes of the veterinary departments; concurrent diseases, host genetic variation, immune suppression, cattle behavior, physiological status, cows scheme form, feeding system, treatments with control program, environments or weather, pathological variations. [33][34][35] Whilst the respiratory disorders, emaciation, rough hair coat, decrease in milk production and presence of reproductive failures shows the most prevalent signs of positive cows in blood and milk groups; the enlargement of lymph nodes, loss of appetites and feces abnormalities manifested the lowers, with presence of some differences between both serum groups. These resultants were approval to studies revealed by various researchers.…”
Section: Discussionmentioning
confidence: 99%
“…32 A variable incidence of bTB may effect through several modes like the geographical position features; Agroecological system; public health condition for humans and animals; herd size, farm management and grazing practice; age, breed, gender and body condition score of animals; compelled organizing schemes of the veterinary departments; concurrent diseases, host genetic variation, immune suppression, cattle behavior, physiological status, cows scheme form, feeding system, treatments with control program, environments or weather, pathological variations. [33][34][35] Whilst the respiratory disorders, emaciation, rough hair coat, decrease in milk production and presence of reproductive failures shows the most prevalent signs of positive cows in blood and milk groups; the enlargement of lymph nodes, loss of appetites and feces abnormalities manifested the lowers, with presence of some differences between both serum groups. These resultants were approval to studies revealed by various researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Mendes et al (2011) examined dairy herds of 15 municipalities and observed that 14% (86/612) of the evaluated animals were positive for the tuberculin test. Milk and blood samples were collected from 401 dairy cattle in 20 properties in the region of Garanhuns, and M. bovis was detected by real-time PCR in one milk sample (0.25%) and eight blood samples (2%); the infected animals originated from 6 of the 20 properties sampled (30%) (CEZAR et al, 2016).…”
Section: Previous Studies Have Been Conducted In 12mentioning
confidence: 99%
“…700 Detection of Mycobacterium tuberculosis complex in cattle ________________________________________ Mycobacterium have been more frequently identified in blood samples of cattle compared to milk and other samples. Cezar et al (2016) reported detection of M. bovis from blood samples in two per cent of cattle maintained in 20 properties in Brazil. They suggested blood PCR as a highly sensitive method for detection of members of MTBC, compared to milk samples.…”
Section: Resultsmentioning
confidence: 99%